Exploring the Drugs/Violence Nexus Among Active Offenders: Contributions From the St. Louis School. (March 2015) - Dickinson, Timothy
In 1985, Paul Goldstein published a seminal article suggesting a conceptual framework for the study of the connection between drugs and violence. This work influenced a generation of scholars, including a number of criminologists from the University of Missouri–St. Louis. Through a series of studies focusing on the collection and analysis of data from active offenders, these criminologists, known as the St. Louis School (SLS), have explicated and expanded Goldstein's initial framework. This article describes the SLS, reviews and integrates its contributions to understanding the drugs/ violence nexus, and suggests fruitful avenues for future research on this pervasive and pernicious relationship.